Korelasi Antara Tecnological Pedagogical And Content Knowladge (TPACK) Dengan Kinerja Mengajar Dosen (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2023)
Abstract This research aims to examine the relationship between the technological, pedagogical, content and knowledge capabilities of lecturers in the IAINsyaikh Abdurrahman Siddik Bangka Belitung environment and lecturer performance. As for the results of this study, there is a positive and significant relationship between Technological Knowledge and the teaching performance of lecturers at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. This is indicated by the calculated correlation coefficient being greater than r table or 0.438 > 0.36 and a significance value of 0.015 0.36 and a significance value of 0.00 0.36 and a significance value of 0.00 0,36 dan nilai signifikansi 0,0150,36 dan nilai signifikansi 0,00 0,36 dan nilai signifikansi 0,00